2005
DOI: 10.1086/498455
|View full text |Cite
|
Sign up to set email alerts
|

The Y Deletion gr/gr and Susceptibility to Testicular Germ Cell Tumor

Abstract: Testicular germ cell tumor (TGCT) is the most common cancer in young men. Despite a considerable familial component to TGCT risk, no genetic change that confers increased risk has been substantiated to date. The human Y chromosome carries a number of genes specifically involved in male germ cell development, and deletion of the AZFc region at Yq11 is the most common known genetic cause of infertility. Recently, a 1.6-Mb deletion of the Y chromosome that removes part of the AZFc region--known as the "gr/gr" del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
158
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 196 publications
(167 citation statements)
references
References 44 publications
5
158
0
4
Order By: Relevance
“…61 In the same study the authors also demonstrated that the deletion affects the spermatogenic potential even in the normal range. gr/ gr deletion has also been reported as a potential risk factor for testicular germ cell tumours, 62 however, this data needs further confirmation in an ethnically and geographically matched casecontrol study setting.…”
Section: Gr/gr Deletionmentioning
confidence: 74%
“…61 In the same study the authors also demonstrated that the deletion affects the spermatogenic potential even in the normal range. gr/ gr deletion has also been reported as a potential risk factor for testicular germ cell tumours, 62 however, this data needs further confirmation in an ethnically and geographically matched casecontrol study setting.…”
Section: Gr/gr Deletionmentioning
confidence: 74%
“…13 Six years later, a major FTC susceptibility gene has yet to be identified, despite substantial additional research. 15,16 The most recent genome-wide linkage analysis reported by the ITCLC did not provide additional support for the hypothesized Xq27 locus, and yielded only modestly interesting LOD scores at other autosomal candidate loci. In this regard, FTC may more closely resemble familial prostate cancer where there is a demonstrated interest in genetic testing, [17][18][19][20] with numerous candidate susceptibility loci having been identified, but to date no major susceptibility genes have been discovered to account for the majority of familial cases.…”
mentioning
confidence: 96%
“…A two fold increased risk of TGCT for "gr/gr" deletion carriers in 1807 affected subjects has been observed with an even higher-three fold-increase in familial cases. 43 In contrast to what would be expected, the authors found that probands from TGCT families exhibiting maternal lineage were at greater risk than those exhibiting paternal lineage. The association between "gr/gr" deletion and TGCT was not confirmed in a separate UK study 42 and an Italian study.…”
Section: The Role Of Somatic Genetic Changesmentioning
confidence: 78%
“…37 In general, the analysis of a very large group of subjects might be more appropriate for detecting genetic predispositions acting at low penetrance than smaller studies, however the situation is more complex for the Y chromosome than for the rest of the genome because of potential biases such as population stratification. 44 Ethnic and geographic matching of cases and controls is fundamental when searching for Y related factors and the multicenter study, 43 although very large, contained only 15% of cases and 23% of unaffected males from designed epidemiologic case-control studies. Moreover, since both gr/gr deletions and familial cases are rare the strength of the large multicenter study is still limited and would require further confirmation.…”
Section: The Role Of Somatic Genetic Changesmentioning
confidence: 99%